The Effectiveness of Service Delivery in Fast Moving Consumer Goods Supply Value Chain: A Case Study of Brands Africa Zambia Limited Company - Kanyamuna, Vincent; Chawapiwa, Oswell; Bwanga, Cynthia (Advances in Social Sciences Research Journal, 2023)
The study focused on analysing the effectiveness of service delivery in fast moving goods supply chains taking Brands Africa as a case study. Some observed supply chain related challenges of Brands Africa that included lower sales volume, high volume of product returns, sale of some expired products out of stock of some product lines and high prices of some merchandise made the study to be mandatory. A pragmatic research paradigm was used in collecting data from a cross-sectional survey sample of 87 respondents and a case study sample of 5 research participants using a survey questionnaire and an in-depth interview guide as research instruments, respectively. The study concluded that supplier contact was strongest on communication with suppliers, importing goods to Zambia and good relationships with suppliers. The study showed Brands Africa had good advertising and merchandising services, and effective marketing research activities in its supply chains The study established that quality of merchandise high, and market image and reputation of Brands Africa was high, and that inventory management, price of merchandise and efficiency of supply chains needed improvement. The study also concluded that there is a significant relationship between supplier contact and marketing contact activities of Brands Africa with the overall satisfaction of its stakeholders. The research recommends Brands Africa to upgrade its product, financial, information and social with its suppliers, transporters, wholesalers and retailers. The study will also guide managers on cost cutting ways, quality management, ensuring efficient operations and maintaining positive image of Brands Africa. The study recommended Brands Africa’s on policy issues like quality of merchandise, quantity of merchandise, price range of merchandise, delivery schedules and communication systems will be improved. The researcher recommends another research to be carried out at national level covering supply chain of other fast-moving consumer goods companies and also considering more independent variables.